Establishment and characterization of primary epithelial cell cultures from healthy canine mammary gland tissue - Nosalova, Natalia; Huniadi, Mykhailo; Valencakova, Alexanda; Hornakova, Lubica; Kalinaj, Blazej; Almasiova, Viera; Marcincakova, Dana; Kubatka, Peter; Hornak, Slavomir; Cizkova, Dasa (Frontiers in Veterinary Science, 2026)
IntroductionIn regenerative medicine and comparative oncology, the development of physiologically relevant in vitro models is critical for advancing our understanding of tissue homeostasis, cellular differentiation, and early tumorigenesis. Such models provide controlled experimental systems to investigate normal mammary gland function, assess responses to therapeutic agents, and establish baseline characteristics for distinguishing healthy from pathological tissue.MethodsThis study successfully established and characterized primary epithelial cell cultures derived from histologically normal canine mammary gland (CMG) tissue. Samples from two healthy female dogs were obtained during elective ovariohysterectomy. Following enzymatic digestion and optimized culture conditions, isolated cells adhered within 24 hours and reached confluence within 6–7 days, maintaining over 95% viability.Results and discussionHistological analysis confirmed either active lactational or regressive tissue states. Cell growth and metabolic activity were evaluated using the CELLigence system and XTT assay, with optimal results achieved at a seeding density of 4,000 cells per well. Immunofluorescence staining confirmed epithelial identity (pan-CK, CK8/18), apical MUC1 expression, low Ki-67 levels and negative expression of mesenchymal markers (vimentin, S100), indicating a healthy, non-cancerous cell population with moderate proliferative activity. This study provides the first detailed protocol for establishing primary CMG epithelial cultures and validates their suitability as a reference model for future oncological studies. Overall, this platform supports translational research, including drug testing and biomarker discovery, contributes to personalized veterinary therapies and enhanced understanding of mammary gland pathology in both dogs and humans.